Molecular Detection of Virulence Factors of Enterococcus Faecalis Isolated From Urine Samples in Duhok City, Kurdistan Region/Iraq. - Khalid, Haval M. (Science Journal of University of Zakho, 2016)
Enterococcus faecalis is one of the leading causes of many infections and mainly urinary tract infections. This pathogen developed high resistance to multiple antibiotics and it harbor many virulence factors genes. This study aimed to determine the antibiotic resistance patterns and screening for some virulence factor genes of E. faecalis isolated from urinary tract infection. Urine samples were collected from 788 outpatient’s clinic having clinical signs of UTI that visited Azadi Teaching Hospital in Duhok city. Urine samples were cultured on bacteriological media and isolated colonies identified using standard bacteriological methods. Antibiotic susceptibility was performed by Kirby Bauer test. All isolates were subjected to species-specific PCR assay for confirmatory identification followed by targeting virulence genes. Twenty five isolates of E. faecalis were detected and confirmed by species-specific PCR assay that expressed high antibiotic-resistance to many selected drugs except norfloxacin, penicillin and ampicillin. The most prevalent genes among all isolates were cpd genes followed by asa1, ace, esp, and gelE. Bearing of virulence genes combination were more frequent among multiple-antibiotic resistant strains. This study highlighted on E. faecalis as causes of UTI in Duhok city that showed multiple resistances to common antibiotics and harboring more than one virulence gene.